Dynamic Crushing Analysis of Hexagonal-Kagome Combined Honeycomb with Negative Poisson’s Ratio - Wei Min Wang; Zhi Liang Yang; Jun Hu (Advances in Materials Science and Engineering)
To enhance the mechanical performances of traditional honeycombs, a novel combined honeycomb (HKH) was proposed based on the regular hexagonal honeycomb (RHH) and Kagome honeycomb (KH). A systematic investigation of the in-plane dynamic crushing behaviors of the honeycombs was conducted via the finite element method, and the crashworthiness characteristics of the three honeycombs were examined. Using one-dimensional shock wave theory and least squares fitting, a fitting formula of the plateau stress was obtained, and the deformation mechanism of the HKH was determined based on the elastic buckling of the cell wall. The results showed that the HKH exhibited a higher plateau stress than the RHH for any velocity impact, while the negative Poisson’s ratio effect was more significant than that of the KH for low-velocity impacts (the peak Poisson’s ratios of the HKH and KH were −0.312 and −0.286, respectively). Furthermore, the effects of the impact velocity and relative density on the energy absorption and auxetic performances were explored. In this study, a novel design was proposed by combining various cell elements to obtain better crashworthiness, providing a new concept to promote the development of lightweight materials.